Green nephrology in practice: actions that promote environmental, social, and economic impact - Fabiana Baggio Nerbass; Rosenilde Schulz; Maicon Aurélio de Vargas; Maycon Truppel Machado; Marcos Alexandre Vieira (Brazilian Journal of Nephrology)
Abstract Climate change affects - and will continue to affect - the overall and kidney health of millions of people worldwide. While healthcare services should be prepared for the increased incidence and changes in the distribution of kidney disease, they also substantially contribute to the depletion of natural resources and greenhouse gas emissions. Among these services, the dialysis sector stands out for its negative environmental impact, due to its high consumption of water, energy, and supplies, in addition to the waste it generates. Thus, measures that reduce the use of natural resources in dialysis procedures, as well as those aimed at reducing the number of patients dependent on dialysis, such as initiatives to prevent kidney disease and encourage kidney transplantation, are of paramount importance. In addition to environmental gains, internal actions focused on the implementation of sustainable practices may also generate economic returns. In this article, our objective was to inform and contribute to the knowledge on sustainable experiences already implemented in a Brazilian philanthropic healthcare institution. Among these, we describe how the use of renewable energy, the reuse of reverse osmosis reject water, and waste recycling translate into reduced operating costs and direct support for socially vulnerable patients.